Corporate entrepreneurship and innovation: A review and future research [Emprendimiento corporativo e innovación: Una revisión y futuras líneas de investigación] (2017)
The Corporate entrepreneurship is a type of activity within organizations that strengthens entrepreneurship and encourages the creation of projects and innovative ideas of high strategic value. The aim of this paper is to analyze the authors with more publications related to corporate entrepreneurship and innovation, in order to detect features that enable the development of entrepreneurial behaviors in organizations. A systematic review of literature of the published articles was conducted as a methodological tool by using databases such as Scopus, Science Direct and Ebsco. The results identify institutional factors in terms of strategy, organizational structure and culture as the most significant in order to understand the relationship between corporate entrepreneurship and innovation to generate new business opportunities in competitive business environments. The main findings of this study also provide some gaps in the existing literature, opening the opportunity to generate new questions and guidelines for future research as key elements of change in modern management practices to stimulate the role of entrepreneurs inside the organizations and creation of business value. © 2017.